Bringing soil chemistry to environmental health science to tackle soil contaminants - Duckworth, Owen W.; Polizzotto, Matthew L.; Thompson, Aaron (Frontiers in Environmental Science, 2022)
With an estimated 5 million sites worldwide, soil contamination is global-scale threat to envi-ronmental and human health. Humans continuously interact with soil, both directly and indirectly, making soils potentially significant sources of exposure to contaminants. Soil chemists are thus a potentially dynamic part of a collaborative cohort attacking environmental health science problems, yet collaborations between soil chemists and environmental heath scientists remain infrequent. In this commentary, we discuss the unique properties of soils that influence contaminants as well as ways that soil chemists can contribute to environmental health research. Additionally, we describe barriers to, and needs for, the integration of soil chemistry expertise in environmental health science research with a focus on the future.